Influence of Corporate Taxpayers Knowledge on Tax Compliance Behaviour under Self-assessment System in Nigeria - Lawan Yahaya; Magaji Abba; Naziru Suleiman (International Journal of Management, Accounting and Economics, 2018)
Self- assessment system (SAS) is system under tax administration that encourages voluntary compliance. This system make it possible for taxpayers to self-assessed themselves and file in accurate tax returns authoritatively. This right could only be exercised if the taxpayers have appropriate knowledge on tax and the system as a whole. This paper intend to explore relationship between corporate taxpayers’ knowledge on SAS and compliance behaviour. A survey questionnaire was distributed to domestic companies in Nigeria whose number were 196 and listed in the Nigerian Stock Exchange. Out of 196 companies, 83 responded and were analyzed using a multiple regression model. The findings in the study, suggest that there is a positive relationship between knowledge on SAS and compliance behaviour which is also significant. The tax authority should increase its education programmes on SAS, to give the taxpayers more knowledge of SAS in the country.